The determinants of asset stripping: theory and evidence from the transition economies - Nauro F. Campos; Francesco Giovannoni (Institute for the Study of Labor (IZA), 2005)
During the transition from plan to market, managers and politicians succeeded in maintaining control of large parts of the stock of socialist physical capital. Despite the obvious importance of this phenomenon, there have been no efforts to model, measure and investigate this process empirically. This paper tries to fill this gap by putting forward theory and econometric evidence. We argue that asset stripping is driven by the interplay between the firm's potential profitability and its ability to influence law enforcement. Our econometric results, for about 950 firms in five transition economies, provide support for this argument.
Keywords: H82; K42; O17; P26; P31; 330; asset stripping; law enforcement; corruption; transition; Öffentliches Unternehmen; Privatisierung; Systemtransformation; Eigentümerstruktur; Korruption; Befragung; Führungskräfte; Osteuropa; Rechtsdurchsetzung